Cystic fibrosis and alpha-1 antitrypsin deficiency: case report and review of literature - Evi Jaspers; Ine Van Dijck; Ilse Hoffman; Noël Knops; Xavier Stéphenne; Peter Witters; Marijke Proesmans (BMC, 2022)
Abstract Background This case report describes a child born with both cystic fibrosis (CF) and alpha-1 antitrypsin deficiency (A1ATD). Both are autosomal recessive inherited diseases, mainly affecting the lungs and the liver. The combination of both diseases together is rare and may lead to a fulminant disease with limited life span. To the best of our knowledge, no case has been reported of a patient born with both diseases. Case presentation After an uneventful pregnancy, a male baby was born with meconium ileus. The suspected diagnosis of CF was confirmed based on the sweat test and genetic analysis. The child developed persisting cholestasis, too severe to be likely caused by CF alone and indicating an associated problem. The diagnosis of A1ATD was established based on clinical suspicion (persisting cholestasis), decreased serum alpha-1 antitrypsin and genetic analysis. Supportive therapy was started, however the boy evolved to rapidly progressive liver disease leading to liver failure which necessitated an infant liver transplantation. Conclusions This case illustrates the complexity of care in case of two severe inherited diseases as well as post solid organ transplant care.